2021
DOI: 10.3390/app11041858
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis of a Tubular Heat Exchanger for the Conditioning of Olive Paste

Abstract: The use of a heat exchanger for the conditioning of the olive paste could enhance the olive oil extraction process. Particularly, paste pre-heating could reduce the malaxation time and, most of all, improve the temperature control during this process (e.g., 27 °C). In this study, a three-dimensional computational fluid dynamics (CFD) analysis of a tubular heat exchanger was carried out to better understand the influence of the inlet conditions of the olive paste on thermal and hydrodynamic behavior within it. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Heat exchangers are used in many food processes for applications such as heating and cooling. CFD was widely used to compare heat exchanger configurations [8], investigate tubular heat exchangers [9][10][11], fouling dynamics [12], designing easyto-clean processing equipment [13] and the possibility of using plate exchangers in a solar pasteurization process [14].…”
Section: Heat Exchangersmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat exchangers are used in many food processes for applications such as heating and cooling. CFD was widely used to compare heat exchanger configurations [8], investigate tubular heat exchangers [9][10][11], fouling dynamics [12], designing easyto-clean processing equipment [13] and the possibility of using plate exchangers in a solar pasteurization process [14].…”
Section: Heat Exchangersmentioning
confidence: 99%
“…In Perone et al, (2021), study of CFD analysis of a tubular heat exchanger used for olive paste conditioning was carried out to evaluate the influence of the inlet conditions of the olive paste on thermal and hydrodynamic behaviour within it. The heat-exchanger-based olive paste conditioning could improve the process of olive oil extraction.…”
Section: Heat Exchangersmentioning
confidence: 99%
“…Although the quality of the olive oil depends on many pre- and post-harvest factors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], over the last twenty years, we have witnessed the need for the latest technological developments in oil processing to improve quality and quantity, but the potential for expansion and growth of the olive processing sector is still great. The process includes cleaning of the olives, crushing to break the cell envelopes of the mesocarp cells and release the oil [ 8 ], conditioning by malaxation to facilitate the grouping of the small oil droplets into larger droplets [ 9 , 10 ], and subsequent mechanical extraction by centrifugation [ 11 ], which is the most common system for separating the olive oil from the olive paste. PEF is considered a non-thermal food processing technology that has been studied to improve mass transfer processes in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…The prefix parameter (tube width) is utilized as an info variable and the yield parameter is the most extreme temperature distinction of container and tube heat exchanger. (Perone et al,2021) showed that the use of a heat exchanger for the conditioning of the olive paste could enhance the olive oil extraction process. Particularly, paste pre-heating could reduce the malaxation time and, most of all, improve the temperature control during this process.…”
Section: Introductionmentioning
confidence: 99%